2022
DOI: 10.1111/all.15312
|View full text |Cite
|
Sign up to set email alerts
|

Single low‐dose exposure to cow’s milk at diagnosis accelerates cow’s milk allergic infants’ progress on a milk ladder programme

Abstract: Background: Cow's milk protein allergy (CMPA) is one of the most common food allergies in infancy. Most infants with CMPA tolerate baked milk from diagnosis and gradually acquire increased tolerance. Nevertheless, parents often display significant anxiety about this condition and a corresponding reluctance to progress with home introduction of dairy due to concerns about possible allergic reactions.Objective: To evaluate the impact on gradual home introduction of foods containing cows' milk after a supervised,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 29 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…The latest study to evaluate the use of the milk ladder as a method of home introduction to milk for those with IgE-mediated CMPA was conducted by d’Art et al and published in April 2022 [ 51 ]. Though this was a randomized trial to evaluate the progression through the milk ladder of infants who received a single dose of the elicited dose of milk (ED05) compared to the control group who did not receive a single dose of ED05, this is also the first published prospective study on the effectiveness of the MAP milk ladder for infants with IgE-mediated CMPA.…”
Section: Home Introduction Of Milk Using a Stepwise Strategy Milk Laddermentioning
confidence: 99%
See 4 more Smart Citations
“…The latest study to evaluate the use of the milk ladder as a method of home introduction to milk for those with IgE-mediated CMPA was conducted by d’Art et al and published in April 2022 [ 51 ]. Though this was a randomized trial to evaluate the progression through the milk ladder of infants who received a single dose of the elicited dose of milk (ED05) compared to the control group who did not receive a single dose of ED05, this is also the first published prospective study on the effectiveness of the MAP milk ladder for infants with IgE-mediated CMPA.…”
Section: Home Introduction Of Milk Using a Stepwise Strategy Milk Laddermentioning
confidence: 99%
“…This is supported by previous single-dose studies of ED05 of peanut and milk; it was evident that recruited families gained significant support and increased confidence from their participation [ 52 ]. This assumption was further supported in the study when it was shown that for the intervention group overall, there was a significant difference in maternal state anxiety between scores at baseline ( M = 37.5, SD = 12.9) and at 6 months ( M = 31.5, SD = 8.6); ( t (32) = −2.81, p = 0.008), whereas no significant difference was found in the control group overall for maternal state anxiety for scores at baseline ( M = 33.1, SD = 8.5) and at 6 months ( M = 31.7, SD = 11.6); ( t (14)4.17, p = 0.59) [ 51 ].…”
Section: Home Introduction Of Milk Using a Stepwise Strategy Milk Laddermentioning
confidence: 99%
See 3 more Smart Citations